2012
DOI: 10.1159/000341566
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Effects of Intraoperative Amino Acid Infusion in Mongrel Dogs

Abstract: Background: Intraoperative amino acid infusion can attenuate the decrease in core temperature, but the metabolic effects are uncertain. Methods: Thirty-six healthy mongrel dogs undergoing ileectomy under general anesthesia were infused intraoperatively with normal saline or 18 compound amino acids at 6, 12, and 24 kJ·kg–1·h–1 (NS, 6-, 12-, and 24-kJ groups) and studied until 24 h after the operation. Blood glucose, plasma insulin, free fatty acids, and triglyceride concentrations were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 71 publications
2
26
0
Order By: Relevance
“…Hyperaminoacidemia and elevated plasma Leu have been linked to increased mTOR activity [10], [22], [23] and PKC pathway activation [71], [72]. These pathways have been linked to activation of protein synthesis consistent with our observations in obese rats.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Hyperaminoacidemia and elevated plasma Leu have been linked to increased mTOR activity [10], [22], [23] and PKC pathway activation [71], [72]. These pathways have been linked to activation of protein synthesis consistent with our observations in obese rats.…”
Section: Discussionsupporting
confidence: 89%
“…[22]. In contradistinction, hyperaminoacidemia in obese Zucker rats was associated with an increase in both protein synthesis and degradation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although this technique is not yet recommended for use in a veterinary clinical setting, studies in humans and dogs have demonstrated safety and effectiveness. 51,52 COMPLICATIONS Complications associated with using techniques to reduce the severity of IPH are usually associated with the specific technique. Patient skin burns are one of the more severe complications and have been associated with heat lamps or defective or inappropriately operated active technique equipment.…”
Section: Metabolic Techniquesmentioning
confidence: 99%
“…The metabolic and thermogenic effects of intraoperative amino acid infusion have also been studied in dogs (Jin et al. ; Clark‐Price et al. ).…”
Section: Introductionmentioning
confidence: 99%